Fault detection during power system out-of-step oscillation using frequency difference sudden-change of voltage and current at a single terminal bus and a novel setting-free distance protection unlocking scheme - Shuai Zhang (Heliyon, 2023)
Setting blocking on the electricity transmission network distance protection is an important control measure to prevent it from malfunctioning in the out-of-step oscillation (OOSO) process. However, this operation makes it lose the ability to cut off faults. Once fault occurs, the consequences are serious, which might bring huge energy loss. How to effectively identify faults and quickly restore its protection capability is an important engineering task, but it's also filled with challenges. For the symmetrical faults occurring at δ≈180∘, the traditional technologies are susceptible to failure because the system seems to be oscillating continuously. For asymmetric faults, the sequence component method can be adopted, but limited by the sequence component extraction speed. Aiming at the above existing problems, this paper launches the targeted study and gives the corresponding solutions. To the former, it innovatively analyzes the variation law about the frequency difference of bus voltage (BV) and system current (SC) before and after fault occurs in the OOSO process, and gives its change range through strict mathematical derivation. Based on this, it proposes a novel one terminal setting-free distance protection unlocking scheme for symmetrical fault. Experiments show that the new variables defined in the criterion change abruptly and last for 3 sampling points after a fault. The new method can effectively identify faults occurring at δ≈180∘. This is an important advantage over the traditional methods. To the latter, it constructs a phasor imaginary part estimator, and proposes a sequence component transient calculation method. It greatly improves the asymmetric fault identification speed of the related method.